Circulation of new lineages of RSV-A and RSV-B in Kuwait shows high diversity in the N- and O-linked glycosylation sites in the G protein between 2020 and 2022 - Madi, Nada; Sadeq, Mohammad; Safar, Hussain A.; Al-Adwani, Anfal; Al-Turab, Mariam (Frontiers in Cellular and Infection Microbiology, 2024)
The human respiratory syncytial virus (RSV) is a significant health concern, particularly for infants, young children, and the elderly. This virus is known to evolve continuously due to environmental factors and herd immunity. In light of this, our study aimed to analyze the genetic variability of the G protein in RSV-A and RSV-B genotypes in Kuwait from 2020 to 2022. Between January 2020 and September 2022, we collected 490 respiratory samples from hospitalized patients with acute respiratory tract infections. These samples were tested and confirmed positive for RSV using multiplex Real-Time PCR. Subsequently, the samples underwent nucleic acid sequencing using the advanced Nanopore sequencing technology to analyze the full-length G gene. Sequence analysis showed that 64 isolates (76%) were RSV-A, and 20 isolates (24%) were RSV-B. The G genes of RSV-A belonged to genotype GA2.3.5, while all the RSV-B genotypes belonged to GB5.0.5a. New lineages and sub-lineages of RSV-A and RSV-B were detected, indicating the circulation of new strains in Kuwait. Many unique and new amino acid changes, including insertions, were found in the G proteins of Kuwaiti isolates, with the highest variability in the second hypervariable region. An increased number of N and O-linked glycosylation sites were also identified in the G protein, which could speculate to alter the antigenicity of RSV. The identified changes in the G protein of RSV-A and RSV-B genotypes might result from immune pressure and could affect the antigenic characteristics of circulating strains in Kuwait. This could potentially lead to new RSV variants that can evade the immune response. Our in-depth analysis of the G proteins of both RSV-A and RSV-B could aid in the development of more potent treatments and vaccines.